Temperature dependence of the Brillouin spectra in Sn₂P₂S(Se)₆ ferroelectric crystals - Yevych, R.M.; Perechinskii, S.I.; Grabar, A.A.; Vysochanskii, Yu.M.; Slivka, V.Yu. (Condensed Matter Physics, 2003)
A temperature dependence of hypersound velocities at transition from a
paraelectric phase to ferroelectric phase in Sn₂P₂S₆ crystals was investigated
by Brillouin scattering spectroscopy. Based on these data, full set of
elastic constants was determined. Similar measurements were also performed
for Sn₂P₂(Se₀.₀₂₈S₀.₇₂)₆ mixed crystals in the paraelectric phase
near a Lifshitz point. The sound velocity indicatrices’ evolution at transition
from Sn₂P₂S₆ to Sn₂P₂(Se₀.₂₈S₀.₀₇₂)₆ was observed and softening of transverse
acoustic phonons in the paraelectric phase near the Lifshitz point
was found. An instability of the acoustic phonons is induced by an interaction
with a soft optic mode which is the origin of an incommensurate phase
appearance in mixed crystals Sn₂P₂(SexS₁−x)₆ with x > xLP = 0.28. Методом розсіювання Мандельштама-Бріллюена досліджено температурну залежність швидкостей гіперзвуку при переході з параелектричної у сегнетоелектричну фазу в кристалах Sn₂P₂S₆. На
основі цих даних визначено повний набір пружних модулів. Такі
ж вимірювання проведені для твердого розчину Sn₂P₂(Se₀.₀₂₈S₀.₇₂)₆
у параелектричній фазі біля точки Ліфшиця. Спостерігається еволюція індикатриси швидкостей при переході від Sn₂P₂S₆ до
Sn₂P₂(Se₀.₂₈S₀.₀₇₂)₆ та зм’якшення поперечного акустичного фонона
в параелектричній фазі біля точки Ліфшиця. Нестабільність акустичного фонона спричинена взаємодією з м’якою оптичною модою,
що є природою виникнення несумірної фази в твердих розчинах
Sn₂P₂(SexS₁−x)₆ з x > xLP = 0.28.